Multidimensional Assessment of Drought and Salinity Tolerance in Six Lamiaceae Species from the Mediterranean Basin (El Tarf, Algeria): Ecological and Agronomic Implications under Climate Change : Multidimensional assessment of drought and salinity tolerance in six Lamiaceae species from the Mediterranean basin (El Tarf, Algeria) under climate change - Smichette, Louiza; Aziz, Nadia Nawel; Nesrine Hacini; Djelloul, Radia; El Melki, Mohamed Nejib (Ethnobotany Research and Applications, 2025)
Background: The Mediterranean Basin, a biodiversity hotspot, faces intensified abiotic stresses, such as drought and salinity, owing to climate change. These conditions pose significant challenges to the sustainable production of medicinal and aromatic plants (MAPs). These plants, especially those in the Lamiaceae family, are vital for traditional knowledge and high-value essential oil (EOs) production. Their production and composition are strongly influenced by environmental factors. Therefore, understanding how MAPs adapt to stress is essential for optimizing cultivation practices and ensuring a reliable supply. Methods: This study evaluated the comparative tolerance of six Lamiaceae species (Lavandula angustifolia, Mentha piperita, Origanum vulgare, Ocimum basilicum, Rosmarinus officinalis, and Salvia officinalis) to progressive drought and salinity stress. Experiments were conducted under controlled conditions, and species selection was guided by ethnobotanical criteria in the El Tarf region of northeastern Algeria, as previously described. Quantitative tolerance indices (Stress Tolerance Index, Tolerance, Yield Stability Index) and the Phenotypic Plasticity Index were used, along with multivariate analyses (PCA) to assess species performance. These tools helped identify critical stress thresholds based on the EO yield and biomass. Results: Origanum vulgare and Rosmarinus officinalis emerged as the most drought-tolerant species, maintaining 98–99% and 97–106% of the control EO yields, respectively, and showing minimal biomass reduction (less than 19%) under moderate drought (50% FC). Lavandula angustifolia exhibited superior salinity tolerance, maintaining 74% of control EO production and surviving as the only species at severe salinity (150 mM NaCl), whereas all other species showed 100% mortality. Conversely, Ocimum basilicum and Mentha piperita were highly sensitive to both stresses, with EO yields dropping to 0% under moderate drought (50% FC) and severe salinity (150 mM NaCl) conditions. Mild stress (75% FC drought, 50 mM NaCl salinity) sometimes induced hormetic responses, with EO accumulation increasing by up to 14.3% in Salvia officinalis. Distinct critical thresholds were identified, including 60–65% FC for drought and 75 mM NaCl for salinity, beyond which EO production sharply declined. Conclusions: This study ranked six Lamiaceae species according to their tolerance to drought and salinity. Origanum vulgare and Rosmarinus officinalis were identified as optimal candidates for cultivation in water-limited environments, whereas Lavandula angustifolia showed the highest potential under saline conditions. These findings provide essential benchmarks for precision agriculture and support strategic water management and cultivar selection to enhance the resilience and productivity of MAPs under climate change conditions. Keywords: Ethnobotany; Lamiaceae; Drought stress; Salinity stress; Essential oil; Tolerance indices; Phenotypic plasticity; Climate change